ANALYSIS OF DEVELOPMENTAL PATTERNS IN WRITING ACQUISITION OF CHINESE STUDENTS - Feng, Xiwu (European Scientific Journal, ESJ, 2015)
The study investigates possible developmental trends in Chinese writing acquisition. Over three hundred Chinese elementary school students were enrolled in one-year empirical study. Writing samples were collected during four separate visits at an interval of three months in order to serve as literacy measure over time. The study examined students’ writing performance during the different time interval as well as writing development in the grade level. An error analysis of students’ writings reveals developmental patterns of using phonological and semantic strategies in solving problems during the writing process. Findings of the study may provide references for educators to the consideration of reevaluating literacy curriculum and pedagogy.